Gender, food and COVID-19: Global stories of harm and hope - Paige Castellanos; Carolyn E. Sachs; Ann R. Tickamyer (Routledge, 2022)
"This book documents how COVID-19 impacts gender, agriculture, and food systems across the globe with on-the-ground accounts and personal reflections from scholars, practitioners, and community members. During the coronavirus pandemic with many people under lockdown, continual agricultural production and access to food remain essential. Women provide much of the formal and informal work in agriculture and food production, distribution, and preparation often under precarious conditions. A cadre of scholars and practitioners from across the globe provide their timely observations on these issues as well as more personal reflections on its impact on their lives and work. Four major themes emerge from these accounts and are interwoven throughout: the pervasiveness of food insecurity, the ubiquity of women's care work, food justice, and policies and research that can that can result in a resilience that reimagines the future for greater gender and intersectional equality. We identify what lessons we can learn from this global pandemic about research and practices related to gender, food, and agricultural systems to strive for more equitable arrangements. This book will be of great interest to students, scholars and practitioners working on gender and food and agriculture during this global pandemic and beyond"
Keywords: 330; Agriculture; agribusiness and food production industries; Development economics and emerging economies; Applied ecology; Central / national / federal government policies; Environmental policy and protocols; Human geography; Sociology; Cultural studies; food and society